A Business-Oriented Approach to Improve Disease Surveillance in Saudi Arabia: A Review - Amani Jafar Alosaif et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Disease surveillance is a cornerstone of public health, particularly in Saudi Arabia, where mass gatherings such as the Hajj pilgrimage pose significant risks for infectious disease transmission. Traditional surveillance systems often face challenges such as delayed reporting, fragmented data, and limited real-time analytics. This review explores how adopting a business-oriented approach—incorporating public-private partnerships (PPPs), digital transformation, cost-effective resource allocation, and stakeholder engagement—can enhance disease surveillance in Saudi Arabia. By leveraging artificial intelligence (AI), cloud computing, and collaborative frameworks, Saudi Arabia can build a more efficient, scalable, and responsive surveillance system aligned with its Vision 2030 goals. Key recommendations include strengthening data governance, investing in workforce training, and fostering international collaborations. This paper highlights successful models from other countries and proposes actionable strategies for Saudi Arabia to modernize its disease surveillance infrastructure. Key words Disease surveillance, Public health, Infectious diseases, Saudi Arabia, Hajj pilgrimage Received Date: February 25, 2024 Accepted Date: March 12, 2024 Published Date: April 17, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/405 https://doi.org/10.5281/zenodo.16937874